The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/agj2.21179
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between the crop yield goal rate and the optimum nitrogen rates for maize production in Mississippi

Abstract: The varying influence of the environment on N supply and demand dictates the need for annually updated fertilizer N recommendations. Currently, crop yield goal (CYG) methods are used by 34 land grant universities, including Mississippi State University, these do not consider environmental variations. This research tested the efficacy of CYG by determining the agronomic optimum N rate (AONR) and the economic optimum N rate for Mississippi corn (Zea mays L.) production. In total, 12 treatments in 2020 and 11 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It is possible to include them and to rely less on the priors if the level of nitrogen applied varied by year as with on-farm experiments (Hegedus and Maxwell, 2022). The amount of nitrogen applied was expected to be greater than the agronomic optimum for most plots (Oglesby et al, 2023) so the plateau would be the only parameter that could be observed for most plots.…”
Section: Future Extensions Of the Approachmentioning
confidence: 99%
“…It is possible to include them and to rely less on the priors if the level of nitrogen applied varied by year as with on-farm experiments (Hegedus and Maxwell, 2022). The amount of nitrogen applied was expected to be greater than the agronomic optimum for most plots (Oglesby et al, 2023) so the plateau would be the only parameter that could be observed for most plots.…”
Section: Future Extensions Of the Approachmentioning
confidence: 99%
“…Lobell et al (2009) and Beza et al (2017) outlined several biophysical factors including nutrient deficiencies, water stress, flooding, planting issues, soil problems, weed pressures, insects, diseases, and lodging, as well as socioeconomic factors such as risk aversion, inexperience, and economic issues. Numerous agronomic strategies exist to improve corn production in Mississippi: substituting crop yield goals (Oglesby et al, 2022) for remote sensing based N management (Dhillon et al, 2020;Sumner et al, 2021), irrigation scheduling using soil moisture sensors (Spencer et al, 2019), crop rotation (Abbas et al, 2012), adopting site-specific optimum plant densities (Williams et al, 2021), proper hybrid selection (Walne & Reddy, 2021;Williams et al, 2020), and optimum planting dates (Williams et al, 2018).…”
Section: Reasons For Yield Gapmentioning
confidence: 99%
“…Corn growth depends on various environmental and management factors, and they significantly affect grain quality (Fornah et al, 2020;Sharma et al, 2023;Oglesby et al, 2023). Oil, protein, and starch are the major quality parameters in corn that determine the overall economic and nutritious value of the crop (Hilliard & Daynard, 1974).…”
Section: Introductionmentioning
confidence: 99%